Crack-resistant polysiloxane dielectric planarization compositions, methods, and films

JP7645959B2Active Publication Date: 2025-03-14ソルスティス アドバンスト マテリアルズ ユーエス インコーポレイティッド
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023177251
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-05
Filing Date
2023-10-13
Publication Date
2025-03-14
Estimated Expiration
2038-12-18

Smart Images

  • Figure 0007645959000013
    Figure 0007645959000013
  • Figure 0007645959000014
    Figure 0007645959000014
  • Figure 0007645959000015
    Figure 0007645959000015
Patent Text Reader

Abstract

To provide materials for planarizing for the surfaces of semiconductor devices which offer heat resistance and crack resistance at temperature of more than 400°C, and also exhibit high optical transmittance.SOLUTION: A composition comprises: a catalyst; at least one solvent; and at least one polysiloxane resin including polysilsesquioxane blocks and polydisiloxane blocks. The polydisiloxane blocks of the polysiloxane resin comprise at least one selected from the group consisting of aryl or alkyl groups with substituted or unsubstituted carbon.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to planarizing materials, and in particular to planarizing dielectric materials for semiconductor and display manufacturing. [Background technology]

[0002] In advanced semiconductor manufacturing, such as microprocessors, memory devices, and displays employing light emitting diodes, there is a need for dielectric materials that can be spin-coated onto the surfaces of devices to fill deep spaces or gaps between device structures and provide a relatively planar surface suitable for subsequent device layer processing.

[0003] Improved planarizing dielectric materials are desired that provide planarization of advanced semiconductor devices with trenches 6 micrometers deep or deeper. Advantageously, such dielectric materials would be crack-resistant at such thicknesses even when exposed to temperatures in excess of 400° C. It is also important for optoelectronic applications that such dielectric materials have high optical transmittance. The dielectric materials should also be thermally stable when exposed to temperatures in excess of 400° C. Summary of the Invention

[0004] A composition for planarizing a semiconductor device surface includes a catalyst, at least one solvent, and at least one polysiloxane resin including a polysilsesquioxane block and a polydisiloxane block. The polydisiloxane block has the general formula: [ka] This is due to In the formula, R1 and R2 are each independently selected from the group consisting of substituted or unsubstituted aryl or alkyl groups having carbon.

[0005] Various embodiments relate to a composition for planarizing a semiconductor device. The composition includes a catalyst, at least one solvent, and at least one polysiloxane resin including a polysilsesquioxane block and a polydisiloxane block. The polydisiloxane block has the general formula: [ka] This is due to In the formula, R1 and R2 each independently represent a substituted or unsubstituted aryl group having carbon. or alkyl groups. In some embodiments, the polydisiloxane block comprises at least one of a poly(diphenylsiloxane) block, a poly(phenylmethylsiloxane) block, and a poly(dimethylsiloxane) block. In some particular embodiments, the polydisiloxane block comprises a poly(diphenylsiloxane) block and a poly(phenylmethylsiloxane) block. In some other embodiments, the polydisiloxane block comprises a poly(dimethylsiloxane) block. In some embodiments, the polysilsesquioxane block comprises at least one of a poly(methylsilsesquioxane) block and a poly(phenylsilsesquioxane) block. In some embodiments, the concentration of the polydisiloxane block is from 0.1 mole percent to 50 mole percent of the polysiloxane resin. In some embodiments, the weight average molecular weight of the polydisiloxane block in the composition is from 100 Da to 5,000 Da. In some embodiments, the at least one solvent comprises at least one of ethyl lactate, propylene glycol propyl ether, propylene glycol monomethyl ether acetate, ethanol, isopropyl alcohol, and n-butyl acetate. In some embodiments, the catalyst comprises at least one of tetramethylammonium acetate, tetramethylammonium hydroxide, tetrabutylammonium acetate, cetyltrimethylammonium acetate, and tetramethylammonium nitrate. In some embodiments, the composition further comprises a surfactant. In some embodiments, the composition further comprises a crosslinker. In some embodiments, the at least one polysiloxane resin comprises a first polysiloxane resin and a second polysiloxane resin. In some embodiments, the at least one polysiloxane resin is a first polysiloxane resin and further comprises a second polysiloxane resin, the second polysiloxane resin being comprised of a poly(silsesquioxane) resin.

[0006] Various embodiments relate to a method for making a planarizing composition. The method includes dissolving at least one polysiloxane resin in one or more solvents to form a resin solution and adding a catalyst to the resin solution. The at least one polysiloxane resin includes a polysilsesquioxane block and a polydisiloxane block. The polydisiloxane block has the general formula: [ka] This is due to wherein R1 and R2 are each independently selected from the group consisting of substituted or unsubstituted carbon-containing aryl or alkyl groups. In some embodiments, the polydisiloxane block comprises at least one of a poly(diphenylsiloxane) block, a poly(phenylmethylsiloxane) block, and a poly(dimethylsiloxane) block. In some embodiments, the concentration of the polydisiloxane block is from 0.1 mole percent to 50 mole percent of the polysiloxane resin.

[0007] Various embodiments relate to a planarization film for semiconductor devices. The planarization film includes a catalyst residue and a cured polysiloxane. The cured polysiloxane includes a polysilsesquioxane block and a polydisiloxane block. The polydisiloxane block has the general formula: [ka] This is due to wherein R1 and R2 are each independently selected from the group consisting of aryl or alkyl groups having substituted or unsubstituted carbon. In some embodiments, the polydisiloxane block comprises at least one of a poly(diphenylsiloxane) block, a poly(phenylmethylsiloxane) block, and a poly(dimethylsiloxane) block. In some embodiments, the weight average molecular weight of the polydisiloxane block is from 100 Da to 5,000 Da. In some embodiments, the concentration of the polydisiloxane block is from 0.1 mole percent to 50 mole percent of the polysiloxane resin.

[0008] The above-mentioned and other characteristics and advantages of the present invention, as well as the manner in which they are achieved, will become more apparent, and the invention itself will be better understood, by referring to the following description of embodiments of the invention in light of the accompanying drawings, in which: [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic cross-sectional view of a portion of a semiconductor device showing the surface topography to be planarized.

[0010] [Diagram 2] 2 is a schematic cross-sectional view of a portion of the semiconductor device of FIG. 1 illustrating planarization of surface topography by a planarization film according to an embodiment of the present disclosure.

[0011] [Diagram 3] FIG. 10 shows thermogravimetric analysis results for a planarization film according to an embodiment of the present disclosure, for Example 15 below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Embodiments of the present disclosure may employ compositions comprising polysiloxane resins comprising polysilsesquioxane blocks and polydisiloxane blocks as described below to coat on the surface of semiconductor devices, such as microprocessors, memory devices, and displays employing light-emitting diodes or other types of displays, to planarize the semiconductor device surface. The coating may be applied, for example, by spin coating or slot coating. Planarized films formed by cured compositions according to embodiments of the present disclosure have been found to exhibit excellent crack resistance at thicknesses greater than 7 micrometers, even when exposed to temperatures in excess of 400° C. Planarized films formed by cured compositions according to some embodiments of the present disclosure have been found to exhibit excellent crack resistance at thicknesses greater than 10 micrometers, even when exposed to temperatures of 380° C. Planarized films formed by cured compositions according to embodiments of the present disclosure have also been found to exhibit high hardness and high optical transparency. Planarized films formed by cured compositions according to embodiments of the present disclosure have also been found to be thermally stable when exposed to temperatures of 360° C. for 24 hours.

[0013] FIGURE 1 is a schematic cross-sectional view of a portion of a semiconductor device showing the surface topography to be planarized. FIGURE 1 shows a semiconductor device 10 including a substrate 12 and at least one surface feature 14. Substrate 12 may be, for example, silicon, silicon dioxide, silicon nitride, aluminum, copper, or may include any other materials in various layers of various thicknesses and arrangements desired for semiconductor device 10. In some embodiments, surface feature 14 may be a trench formed in substrate 12.

[0014] Surface feature 14 may be described as having a width W and a depth D. In some embodiments, the depth D of surface feature 14 may be as shallow as 0.01 micrometers, 0.1 micrometers, 0.5 micrometers, or 1 micrometer, or as deep as 3 micrometers, 5 micrometers, 10 micrometers, 100 micrometers. In some embodiments, the depth D of surface feature 14 may range from 0.01 micrometers to 100 micrometers, 0.1 micrometers to 10 micrometers, 0.5 micrometers to 5 micrometers, or 1 micrometer to 3 micrometers. In some embodiments, the width W of surface feature 14 may be as small as 0.01 micrometers, 0.1 micrometers, 1 micrometer, 10 micrometers, or as large as 50 micrometers, 100 micrometers, 500 micrometers, 1000 micrometers. In some embodiments, the width W of the surface feature 14 can be in the range of 0.01 micrometers to 1000 micrometers, 0.1 micrometers to 500 micrometers, 1 micrometer to 100 micrometers, or 10 micrometers to 50 micrometers.

[0015] FIG. 2 is a schematic cross-sectional view of a portion of the semiconductor device 10 of FIG. 1 illustrating planarization of surface features 14 by a planarizing film 16 according to an embodiment of the present disclosure. FIG. 2 illustrates the semiconductor device 10 after forming a planarizing film 16 from a composition including a polysiloxane resin according to an embodiment of the present disclosure. The planarizing film 16 fills the surface features 14 to provide a substantially planar surface 18 upon which subsequent device layers (not shown) may be formed. In some embodiments, the planarizing film 16 can have a thickness T over a portion of the semiconductor device 10 that is greater than 6 micrometers. In some embodiments, the planarizing film 16 can have a thickness T over a portion of the semiconductor device 10 that is greater than 10 micrometers.

[0016] 1 and 2 show one example in which a planarization film 16 may be formed according to an embodiment of the present disclosure. It is understood that a planarization film 16 according to an embodiment of the present disclosure may be formed over many other microstructures with different arrangements of conductive, non-conductive, and semiconductive materials. For ease of illustration, only one surface feature 14 is shown in FIGS. 1 and 2. However, it is understood that an embodiment may include multiple surface features 14.

[0017] The planarization film 16 can be formed by coating at least a portion of the semiconductor device 10, for example, by spin coating or slot coating with a composition comprising at least one solvent, a catalyst, and a polysiloxane resin, as described below. In some embodiments, the composition can further comprise a surfactant. In some embodiments, the composition can further comprise a crosslinker. In some embodiments, the composition consists essentially of a composition comprising at least one solvent, a catalyst, a surfactant, and at least one polysiloxane resin, as described below. In some embodiments, the composition consists essentially of a composition comprising at least one solvent, a catalyst, a surfactant, a crosslinker, and at least one polysiloxane resin, as described below.

[0018] In some embodiments, the polysiloxane resin may include a polysilsesquioxane block and a polydisiloxane block. The polysilsesquioxane block has the formula [RSiO 3 / 2 ] n In some embodiments, the polysilsesquioxane may include any type of polysilsesquioxane having the formula: In an embodiment, the polysilsesquioxane blocks can include poly(methylsilsesquioxane) blocks, poly(phenylsilsesquioxane) blocks, poly(methylphenylsilsesquioxane), or any combination thereof.

[0019] The polydisiloxane blocks have the formula: Formula I: [ka] This is due to In the formula, R1 and R2 are each independently selected from the group consisting of substituted or unsubstituted aryl or alkyl groups having carbon.

[0020] For example, in some embodiments, the polydisiloxane block can include a poly(diphenylsiloxane) block where R1 and R2 are each a phenyl group. In some embodiments, the polydisiloxane block can include a poly(dimethylsiloxane) block where R1 and R2 are each a methyl group. In some embodiments, the polydisiloxane block can include a poly(phenylmethylsiloxane) block where R1 is a phenyl group and R2 is a methyl group.

[0021] In some embodiments, the polysiloxane resin may comprise a single type of polydisiloxane block. For example, in some embodiments, the polydisiloxane block comprises a poly(dimethylsiloxane) block, such as in SST-3PM2 dimethylsiloxane copolymer resin available from Gelest Inc. (Morrisville, Pennsylvania). In other embodiments, the polysiloxane resin may comprise multiple types of polydisiloxane blocks. For example, in some embodiments, the polydisiloxane block may comprise any combination of poly(diphenylsiloxane) blocks, poly(dimethylsiloxane) blocks, or poly(phenylmethylsiloxane) blocks. In some embodiments, the polydisiloxane block may comprise a poly(diphenylsiloxane) block and a poly(phenylmethylsiloxane) block, such as in SST-3PM4 tetrapolymer resin available from Gelest Inc. (Morrisville, Pennsylvania). In some other embodiments, the polydisiloxane blocks can consist of poly(diphenylsiloxane) blocks, poly(dimethylsiloxane) blocks, and poly(phenylmethylsiloxane) blocks.

[0022] The polydisiloxane blocks in the polysiloxane resin can have a weight average molecular weight (Mw). In some embodiments, the weight average molecular weight (Mw) of the polydisiloxane in the composition is as low as 100 Da, 200 Da, 500 Da, 800 Da, 1,000 Da, or 1,200 Da, or as high as 1,600 Da, 2,100 Da, 2,600 Da, 3,400 Da, 4,300 Da, or 5,000 Da, or within any range defined by any two of the foregoing values. For example, in some embodiments, the Mw of the polydisiloxane blocks in the composition ranges from 100 Da to 5,000 Da, 200 Da to 4,300 Da, 1,000 Da to 2,100 Da, 1,200 Da to 4,300 Da, or 1,200 Da to 1,600 Da. In some embodiments, the Mw of the polydisiloxane blocks in the composition is about 1,300 Da. This can be measured by gel permeation chromatography, as is known in the art.

[0023] In some embodiments, the concentration of polydisiloxane blocks in the polysiloxane resin can be as low as 0.1 mole percent (mol %), 1 mol %, 10 mol %, or 20 mol %, or as high as 25 mol %, 30 mol %, 35 mol %, 40 mol %, or 50 mol % of the polysiloxane resin, or within any range defined by any two of the foregoing values; for example, in some embodiments, the concentration of polydisiloxane blocks in the composition can be in the range of 0.1 mol % to 50 mol %, 1 mol % to 45 mol %, 10 mol % to 40 mol %, or 20 mol % to 30 mol % of the polysiloxane resin.

[0024] Without wishing to be bound by any theory, it is believed that the long chain structure in the polysiloxane resins described herein Polydisiloxane Block It is believed that the flexibility provided by provides stress relief between the relatively rigid polysilsesquioxane blocks. Polydisiloxane BlockThe use of provides additional flexibility by limiting the opportunity for crosslinking of the polymer resin, as compared to, for example, polytrisiloxane or polytetrasiloxane blocks. Furthermore, such films without stress relief are believed to be more susceptible to cracking due to the buildup of high stress in the film. Thus, planarized films formed from compositions according to embodiments of the present disclosure are capable of resisting cracking even at thicknesses greater than 7 micrometers and after exposure to temperatures greater than 400°C.

[0025] In some embodiments, the at least one polysiloxane resin can be any one of the polysiloxane resins described above. In other embodiments, the at least one polysiloxane resin can include a first polysiloxane resin and a second polysiloxane resin different from the first polysiloxane resin. In some embodiments, the first polysiloxane resin and the second polysiloxane resin are each one of the polysiloxane resins described above. In other embodiments, the first polysiloxane resin can be one of the polysiloxane resins described above, and the second polysiloxane resin can be a poly(silsesquioxane) resin that is not one of the polysiloxane resins described above, such as a poly(phenyl-methylsilsesquioxane) resin.

[0026] The at least one solvent may include a single solvent such as glycol ether, glycol ether acetate, n-butyl acetate, a ketone, or an alcohol. The glycol ether may include, for example, propylene glycol propyl ether or propylene glycol methyl ether. The glycol ether acetate may include, for example, propylene glycol methyl ether acetate (PGMEA), 2-ethoxyethyl acetate, or 2-methoxyethyl acetate. The ketone may include, for example, acetone or diethyl ketone. The alcohol may include, for example, isopropyl alcohol, butanol, or ethanol. In other embodiments, the at least one solvent includes a mixture of two or more of the aforementioned solvents.

[0027] The catalyst may include, for example, tetramethylammonium acetate (TMAA), tetramethylammonium hydroxide (TMAH), tetrabutylammonium acetate (TBAA), cetyltrimethylammonium acetate (CTAA), tetramethylammonium nitrate (TMAN), triphenylamine, trioctylamine, tridodecylamine, triethanolamine, tetramethylphosphonium acetate, tetramethylphosphonium hydroxide, triphenylphosphine, trimethylphosphine, trioctylphosphine, aminopropyltriethoxysilane, aminopropyltriethoxysilane triflate, and any combination thereof. Such catalysts may be activated by heat to induce polymerization and polymerization of the composition after the composition is applied to the semiconductor device 10. Crosslinking can occur to form the planarizing film 16 .

[0028] In some embodiments, the composition can further include a surfactant. It has been found that the surfactant can further reduce striations, which can be particularly useful when the composition is spin-coated onto a larger diameter semiconductor device wafer or display substrate. In some embodiments, the surfactant can be a polyether-modified polydimethylsiloxane surfactant, such as BYK®-306 or BYK®-307, available from BYK-Chemie (Wesel, Germany).

[0029] In some embodiments, the concentration of the surfactant in the composition can be as low as 0.01%, 0.1%, 0.4%, 0.6%, or 0.8% by weight, or as high as 1%, 5%, 10%, 15%, or 20% by weight of the total weight of the composition, or within any range defined by any two of the foregoing values; for example, in some embodiments, the concentration of the surfactant in the composition can be in the range of 0.01% to 20% by weight, 0.1% to 15% by weight, 0.4% to 10% by weight, 0.6% to 5% by weight, or 0.8% to 1% by weight of the total weight of the composition.

[0030] In some embodiments, the composition may further include an organic acid that may volatilize or decompose at elevated temperatures to aid in stabilizing the composition. In some embodiments, the organic acid may include trifluoroacetic acid, p-toluenesulfonic acid, citric acid, formic acid, or acetic acid, or any combination thereof. In some embodiments, the concentration of the organic acid may be as little as 0.01%, 0.1%, 0.2%, or 0.4% by weight of the total weight of the composition, or as much as 0.5%, 0.6%, 0.8%, or 1% by weight, or within any range defined by any two of the preceding values, for example, in some embodiments, the concentration of the organic acid in the composition may be in the range of 0.01% to 1%, 0.1% to 0.8%, 0.3% to 0.6%, or 0.4% to 0.5% by weight of the total weight of the composition.

[0031] In some embodiments, the composition may further include a crosslinking agent. The crosslinking agent forms bonds in the polysiloxane resin. Without wishing to be bound by any theory, it is believed that the bonds provided by the crosslinking agent provide additional structure and strength to the planarization film 16, which provides additional crack resistance. In some embodiments, the crosslinking agent may include bis-(trimethoxysilylpropyl)amine, 1,3 bis(triethoxysilyl)benzene, 1,4 bis(triethoxysilyl)benzene, 2,6-bis(triethoxysilyl)-naphthalene, 9,10-bis(triethoxysilyl)-anthracene, 1,6-bis(trimethoxysilyl)-pyrene, bis(triethoxysilyl)methane, 1,2-bis(triethoxysilyl)ethane, or 1-(triethoxysilyl)-2-(diethoxymethylsilyl)ethane, or any combination thereof.

[0032] A method of making a planarizing composition according to an embodiment of the present disclosure may include providing at least one polysiloxane resin as described above, and dissolving the polysiloxane resin in one or more solvents to form a resin solution. Dissolution of the polysiloxane resin may be facilitated by mixing the polysiloxane resin in the one or more solvents for 1-4 hours. A catalyst as described above may be added to the resin solution. In some embodiments, a surfactant as described above may also be added to the resin solution. The resin solution may be stirred for another few hours, for example 3 hours, to form a composition. The composition may then be filtered through a 0.1 micrometer filter.

[0033] In use, the planarizing composition according to embodiments of the present disclosure is applied, for example by spin coating, to a The planarizing composition can be applied to the semiconductor device 10 (FIG. 1) by baking at a temperature ranging from about 160° C. to about 180° C. to drive off substantially all of the at least one solvent and form an uncured film. In some embodiments, once the at least one solvent has been substantially driven off, a second coating of the planarizing composition can be applied over the coated uncured film and the semiconductor device 10, which has been baked again at a temperature ranging from about 160° C. to about 180° C. to drive off substantially all of the at least one solvent and form a second layer of uncured film. The coating and backing process can be completed until a desired thickness of the uncured film is achieved, after which a catalyst can be activated by heat to cure the film by polymerizing and crosslinking the polysiloxane resin to form the planarizing film 16. Residues of the catalyst can remain after curing.

[0034] In some embodiments, the planarizing film 16 may be cured at temperatures as low as 250°C, 260°C, 280°C, 300°C, or 350°C, or as high as 400°C, 410°C, 420°C, 430°C, 440°C, or 450°C, or any temperature between any two of the aforementioned temperatures. For example, in some embodiments, the planarizing film 16 may be cured at temperatures ranging from 250°C to 450°C, 260°C to 440°C, 280°C to 430°C, 300°C to 420°C, or 350°C to 410°C.

[0035] In some embodiments, the planarizing film 16 may further include a surfactant residue according to any of the above embodiments, including a residue of a polyether modified polydimethylsiloxane surfactant such as BYK®-307.

[0036] While this invention has been described with respect to exemplary designs, the invention can be further modified within the spirit and scope of the disclosure, and this application is intended to cover such departures from the present disclosure as come within known or customary practice in the art to which this invention pertains. EXAMPLES

[0037] Example 1 - Comparative Example - GR150F Poly(silsesquioxane) Resin In a 200 mL flask, 10 g of BYK®-307 surfactant from BK-Chemie was added to 90 g of ethanol and stirred at room temperature for 1 hour to prepare a 10 wt% surfactant solution. In a 100 mL flask, 0.5 g of tetramethylammonium nitrate (TMAN) catalyst was added to 24.5 g of deionized water and stirred at room temperature for 1 hour to prepare a 2 wt% TMAN catalyst solution. In another 200 mL flask, 45.0 g of GR150F resin from Techneglas (Perrysburg, Ohio) was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a GR150F resin solution. GR150 is a poly(silsesquioxane) resin containing equimolar amounts of poly(methylsilsesquioxane) and poly(phenylsilsesquioxane) blocks with approximately 0.3 mol% of poly(dimethylsiloxane) blocks. In a separate 200 mL flask, 1.25 g of the 10 wt % surfactant solution and 0.8 g of the TMAN catalyst solution were added to 100 g of the GR150F solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0038] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin coating at 1,500 revolutions per minute (RPM). The wafer with the cast film was baked on two successive hot plates (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) in an air atmosphere for 60 seconds each to evaporate the solvent. The wafer with the baked coating was then dried in a nitrogen atmosphere for 20 minutes. The coating was cured at 350° C. for 1 hour in a 350° C. oven. The cured coating was inspected for cracks by optical and scanning electron microscopy. Severe cracking of the cured coating was observed. Example 2 - Comparative Example - Poly(silsesquioxane) Resin SST-3PM1

[0039] In a 200 mL flask, 45.0 g of SST-3PM1 resin obtained from Gelest Inc. (Morrisville, Pennsylvania) was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM1 resin solution. SST-3PM1 is a polysilsesquioxane resin containing 90 mol % poly(phenylsilsesquioxane) blocks and 10 mol % poly(methylsilsesquioxane) blocks. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared as above and 0.8 g of the TMAN catalyst solution prepared as above were added to 100 g of the SST-3PM1 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0040] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured and found to be 28,439 Å. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen ambient. The cured coating was inspected for cracks by optical and scanning electron microscopy. No cracks in the cured coating were observed. Example 3 - Dimethylsiloxane Copolymer Resin SST-3PM2

[0041] In a 200 mL flask, 45.0 g of SST-3PM2 resin obtained from Gelest Inc. (Morrisville, Pennsylvania) was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM2 resin solution. SST-3PM2 is a dimethylsiloxane copolymer containing 70 mol % poly(phenylsilsesquioxane) block and 30 mol % poly(dimethylsiloxane) copolymer block. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared as above and 0.8 g of the TMAN catalyst solution prepared as above were added to 100 g of the SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0042] The filtered planarization composition was coated on a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air atmosphere (the first hot plate with a surface temperature of 160° C. and the second hot plate with a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen atmosphere. The cured coating was inspected for cracks by optical and scanning electron microscopy. No cracks in the cured coating were observed. Example 4 - Dimethylsiloxane Copolymer Resin SST-3PM4

[0043] In a 200 mL flask, 45.0 g of SST-3PM4 resin obtained from Gelest Inc. (Morrisville, Pennsylvania) was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM4 resin solution. SST-3PM4 contains 45 mol % poly(methylsilsesquioxane) blocks, 40 mol % poly(phenylsilsesquioxane) blocks, 15 mol % poly(phenylmethylsiloxane) blocks, and 10 mol % poly(diphenylsiloxane) blocks. Dimethylsiloxane copolymer resin. In a separate 200 mL flask, 1.25 g of the 10 wt% surfactant solution prepared above and 0.8 g of the TMAN catalyst solution prepared above were added to 100 g of the SST-3PM4 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0044] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured and found to be 32,556 Å. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen ambient. The cured coating was inspected for cracks by optical and scanning electron microscopy. No cracks in the cured coating were observed. Example 5 - Poly(silsesquioxane) resin GR150F and dimethylsiloxane copolymer resin SST-3PM2

[0045] In a 200 mL flask, 45.0 g of GR150F resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a GR150F resin solution. In another 200 mL flask, 45.0 g of SST-3PM2 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above and 0.8 g of the TMAN catalyst solution prepared above were added to 95 g of GR150F resin solution and 5 g of SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0046] The filtered planarization composition was coated on a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air atmosphere (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured and found to be 32,425 Å. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen atmosphere. The cured coating was inspected for cracks by optical and scanning electron microscopy. Cracking of the cured coating was observed. The cracking was to a lesser extent than that observed in Comparative Example 1. Example 6 - Poly(silsesquioxane) resin GR150F and dimethylsiloxane copolymer resin SST-3PM2

[0047] In a 200 mL flask, 45.0 g of GR150F resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a GR150F resin solution. In another 200 mL flask, 45.0 g of SST-3PM2 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above and 0.8 g of the TMAN catalyst solution prepared above were added to 75 g of GR150F resin solution and 25 g of SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0048] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was then placed on a hot plate in succession in an air environment (the first hot plate had a surface temperature of 160° C.). The wafer was baked on a hot plate (first hot plate and a second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured and found to be 32,790 Å. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen atmosphere. The cured coating was inspected for cracks by optical microscopy and scanning electron microscopy. Cracking of the cured coating was observed. The cracking was to a lesser extent than that observed in Comparative Example 1. Example 7 - Poly(silsesquioxane) resin SST-3PM1 and dimethylsiloxane copolymer resin SST-3PM2

[0049] In a 200 mL flask, 30.0 g of SST-3PM1 resin was added to 70.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM1 resin solution. In another 200 mL flask, 30.0 g of SST-3PM2 resin was added to 70.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above and 0.8 g of the TMAN catalyst solution prepared above were added to 100 g of SST-3PM1 resin solution and 1 g of SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0050] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured and found to be 12,942 Å. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen ambient. The cured coating was inspected for cracks by optical and scanning electron microscopy. No cracks in the cured coating were observed. Example 8 - Poly(silsesquioxane) resin SST-3PM1 and dimethylsiloxane copolymer resin SST-3PM4

[0051] In a 200 mL flask, 45.0 g of SST-3PM1 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM1 resin solution. In another 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM4 resin solution. In another 200 mL flask, 0.5 g of the 10 wt % surfactant solution prepared above and 0.32 g of the TMAN catalyst solution prepared above were added to 10 g of SST-3PM1 resin solution and 30 g of SST-3PM4 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0052] The filtered planarization composition was coated on two 4-inch silicon wafers by spin-coating at 1,500 RPM. The wafers with the cast films were baked on two successive hot plates in air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured for each wafer and found to be 31,873 Å and 31,915 Å. One of the wafers was cured at 410° C. for 30 minutes in a nitrogen ambient and the other was cured at 450° C. for 30 minutes in a nitrogen ambient. The cured coatings were inspected for cracks by optical and scanning electron microscopy. No cracks were observed in the cured coating on any of the wafers. Example 9 - Poly(silsesquioxane) resin SST-3PM1 and dimethylsiloxane copolymer resin SST-3PM4

[0053] In a 200 mL flask, 45.0 g of SST-3PM1 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM1 resin solution. In another 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM4 resin solution. In another 200 mL flask, 0.5 g of the 10 wt % surfactant solution prepared above and 0.32 g of the TMAN catalyst solution prepared above were added to 20 g of SST-3PM1 resin solution and 20 g of SST-3PM4 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0054] The filtered planarization composition was coated on two 4-inch silicon wafers by spin-coating at 1,500 RPM. The wafers with the cast films were baked on two successive hot plates in air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured for each wafer and found to be 31,897 Å and 31,896 Å. One of the wafers was cured at 410° C. for 30 minutes in a nitrogen ambient and the other was cured at 450° C. for 30 minutes in a nitrogen ambient. The cured coatings were inspected for cracks by optical and scanning electron microscopy. No cracks were observed in the cured coating on either wafer. Example 10 - Poly(silsesquioxane) resin SST-3PM1 and dimethylsiloxane copolymer resin SST-3PM4

[0055] In a 200 mL flask, 45.0 g of SST-3PM1 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM1 resin solution. In another 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM4 resin solution. In another 200 mL flask, 0.5 g of the 10 wt % surfactant solution prepared above and 0.32 g of the TMAN catalyst solution prepared above were added to 30 g of SST-3PM1 resin solution and 10 g of SST-3PM4 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0056] The filtered planarization composition was coated on two 4-inch silicon wafers by spin-coating at 1,500 RPM. The wafers with the cast films were baked on two successive hot plates in air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured for each wafer and found to be 31,684 Å and 31,722 Å. One of the wafers was cured at 410° C. for 30 minutes in a nitrogen ambient and the other was cured at 450° C. for 30 minutes in a nitrogen ambient. The cured coatings were inspected for cracks by optical and scanning electron microscopy. No cracks were observed in the cured coating on any of the wafers. Example 11 - Dimethylsiloxane Copolymer Resins SST-3PM2 and SST-3PM4

[0057] In a 200 mL flask, 30.0 g of SST-3PM4 resin was added to 70.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM4 resin solution. In another 200 mL flask, 30.0 g of SST-3PM2 resin was added to 70.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above and the above 0.8 g of the TMAN catalyst solution prepared as above was added to 100 g of the SST-3PM4 resin solution and 1 g of the SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0058] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured and found to be 14,231 Å. The wafer with the baked coating was cured at 350° C. for 1 hour in a nitrogen ambient. The cured coating was inspected for cracks by optical and scanning electron microscopy. No cracks in the cured coating were observed. Example 12 - Dimethylsiloxane Copolymer Resins SST-3PM2 and SST-3PM4

[0059] In a 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM4 resin solution. In another 200 mL flask, 45.0 g of SST-3PM2 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form a SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above and 0.8 g of the TMAN catalyst solution prepared above were added to 100 g of SST-3PM4 resin solution and 1 g of SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarization composition. The planarization composition was filtered through a 0.1 micrometer filter.

[0060] The filtered planarization composition was coated by spin coating onto five 4-inch silicon wafers, two at 1,000 RPM, two at 1,500 RPM, and one at 2,400 RPM. The wafers with the cast films were baked on two successive hot plates (the first hot plate with a surface temperature of 160° C. and the second hot plate with a surface temperature of 180° C.) in an air environment for 60 seconds each to evaporate the solvent. One of the two wafers coated at 1,000 RPM, one of the two wafers coated at 1,500 RPM, and the wafer coated at 2,400 RPM each received a second coating, each spun at the same speed as the first coating, and baked again on the hot plates as above. The thickness of the baked coating was measured on several wafers and found to be 43,458 Å for the single coating at 1,000 RPM, 93,494 Å for the double coating at 1,000 RPM, 32,440 Å for the single coating at 1,500 RPM, and 54,973 Å for the double coating at 2,400 RPM. Five wafers with baked coatings were cured at 410° C. for 30 minutes in a nitrogen ambient. The cured coatings were inspected for cracks by optical and scanning electron microscopy. No cracks were observed in the cured coating on wafers with coating thicknesses up to 54,973 Å. Cracking was observed only on the wafer with a coating thickness of 93,494 Å. Example 13 - Dimethylsiloxane Copolymer Resins SST-3PM2 and SST-3PM4

[0061] In a 100 mL flask, 0.5 g of tetrabutylammonium nitrate (TBAA) catalyst was added to 24.5 g of deionized water and stirred at room temperature for 1 hour to prepare a 2 wt% TBAA catalyst solution. In a 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM4 resin solution. In another 200 mL flask, 45.0 g of SST-3PM2 resin was added to 55. 0 g of PGMEA and stirred at room temperature for 1 hour to form SST-3PM2 resin solution. In a separate 200 mL flask, 0.675 g of the 10 wt % surfactant solution prepared above, 0.4 g of TBAA catalyst solution, and 0.025 g of trifluoroacetic acid were added to 50 g of SST-3PM4 resin solution and 0.5 g of SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0062] The filtered planarization composition was coated by spin coating onto three 4-inch silicon wafers, one at 600 RPM, one at 1,000 RPM, and one at 1,500 RPM. The wafers with the cast film were baked on two successive hot plates in air ambient (the first hot plate with a surface temperature of 160° C. and the second hot plate with a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The thickness of the baked coating was measured on these wafers and found to be 37,020 Å for the single coating at 1,500 RPM and 50,012 Å for the single coating at 1,000 RPM. It was not possible to measure the thickness of the single coating at 600 RPM because the spin speed was too slow to produce a uniform coating. The three wafers with the baked coating were cured at 410° C. for 30 minutes in a nitrogen ambient. The cured coatings were inspected for cracks by optical and scanning electron microscopy. No cracking of the cured coating was observed on the wafers coated at 1,500 RPM. Cracking was observed on the wafers coated at 1,000 RPM. Example 14 - Dimethylsiloxane Copolymer Resins SST-3PM2 and SST-3PM4

[0063] In a 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM4 resin solution. In another 200 mL flask, 45.0 g of SST-3PM2 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above, 0.8 g of the TMAN catalyst solution prepared above, and 0.45 g of a crosslinker were added to 100 g of the SST-3PM4 resin solution and 1 g of the SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The crosslinker was Momentive Performance Polymers. The planarizing composition was Silquest® A-1170 (bis-(trimethoxysilylpropyl)amine) obtained from Materials, Waterford, N.Y. The planarizing composition was filtered through a 0.1 micrometer filter.

[0064] The filtered planarization composition was coated by spin coating onto twelve 4-inch silicon wafers, three at 1,000 RPM, three at 1,300 RPM, three at 1,800 RPM, and three at 2,400 RPM. The wafers with the cast film were baked on two successive hot plates in an air atmosphere (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. Each of the wafers received a second coating, each spun at the same speed as the first coating, and baked again on the hot plates as above. The thickness of the baked coating was measured and determined for each of the wafers. The twelve wafers were cured in a nitrogen atmosphere for 30 minutes. Four of the twelve wafers, one each of the wafers coated at the four spin speeds, were cured at 360° C. Another four of the twelve wafers, one of each of the four spin speed coated wafers, were cured at 380° C. The remaining four of the twelve wafers, one of each of the four spin speed coated wafers, were cured at 410° C. The cured coatings were inspected for cracks by optical and scanning electron microscopy. The thickness and crack inspection results are shown in Table 1. The results are shown below in Table 1. As shown in Table 1, no cracking of the cured coating was observed on wafers having coating thicknesses greater than 10 micrometers (100,000 Å) at temperatures as high as 380° C. No cracking of the cured coating was observed on wafers having coating thicknesses greater than 7 micrometers (77,679 Å) at temperatures as high as 410° C. [Table 1] Example 15 - Dimethylsiloxane Copolymer Resins SST-3PM2 and SST-3PM4

[0065] In a 200 mL flask, 45.0 g of SST-3PM4 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM4 resin solution. In another 200 mL flask, 45.0 g of SST-3PM2 resin was added to 55.0 g of PGMEA and stirred at room temperature for 1 hour to form an SST-3PM2 resin solution. In another 200 mL flask, 1.25 g of the 10 wt % surfactant solution prepared above, 0.8 g of the TMAN catalyst solution prepared above, and 0.45 g of (bis-(trimethoxysilylpropyl)amine crosslinker above were added to 100 g of the SST-3PM4 resin solution and 1 g of the SST-3PM2 resin solution and stirred at room temperature for 3 hours to form a planarizing composition. The planarizing composition was filtered through a 0.1 micrometer filter.

[0066] The filtered planarization composition was coated onto a 4-inch silicon wafer by spin-coating at 1,500 RPM. The wafer with the cast film was baked on two successive hot plates in an air ambient (the first hot plate having a surface temperature of 160° C. and the second hot plate having a surface temperature of 180° C.) for 60 seconds each to evaporate the solvent. The wafer with the baked coating was cured at 410° C. for 30 minutes in a nitrogen ambient.

[0067] The cured coating was recovered from the wafer and TGA analysis was performed on a Discovery TGA System. The samples were heated in N2 from room temperature (25°C) to approximately 360°C and held for 24 hours. These results are shown in Figure 3, which shows the TGA temperature profile 20 (referring to the right hand axis) and the weight of the coating as a percentage of the initial coating weight 22 (referring to the left hand axis). As shown in Figure 3, the coating is thermally stable, losing less than 1 wt% weight after heating at 360°C for 24 hours.

[0068] In a 100 mL flask, 20.0 g of the planarizing composition was added to 25.0 g of PGMEA and stirred at room temperature for 1 hour to form a diluted planarizing composition. Filtered through a 0.1 micrometer filter.

[0069] The filtered diluted planarization composition was coated on an 8 inch silicon wafer and a 2 inch x 2 inch transparent glass substrate by spin coating at 1,500 RPM. The silicon wafer and glass substrate with the cast film were baked on two successive hot plates in air ambient (the first hot plate with a surface temperature of 160°C and the second hot plate with a surface temperature of 180°C) for 60 seconds each to evaporate the solvent. The wafer with the baked coating was cured at 250°C for 60 minutes in air ambient.

[0070] The transmittance of the glass and coated glass was measured on a Hitachi U-3900 UV-Vis spectrophotometer. The uncoated glass substrate was measured to have a light transmittance of 92.1%, while the cured coating on the glass substrate was measured to have a light transmittance of 91.6%, indicating high transparency of the cured coating.

[0071] The 8-inch silicon wafers with the cured coating were measured for nanohardness and reduced elastic modulus analysis by nanoindentation testing on a Hysitron® Nanomechanical Test System. A high nanohardness of 145.1 Mpa and a reduced elastic modulus of 3.49 GPa were measured for the cured coating on the silicon wafer. The present specification includes the following aspects of the invention. [1] A composition for planarizing a surface of a semiconductor device, comprising: A catalyst; At least one solvent; and at least one polysiloxane resin comprising a polysilsesquioxane block and a polydisiloxane block, wherein the polydisiloxane block has the general formula: [ka] This is due to In the formula, R 1 、R 2 are each independently selected from the group consisting of aryl or alkyl groups having substituted or unsubstituted carbon. [2] The composition according to [1], wherein the polydisiloxane block comprises at least one of a poly(diphenylsiloxane) block, a poly(phenylmethylsiloxane) block, and a poly(dimethylsiloxane) block. [3] The composition according to [1], wherein the polysilsesquioxane block comprises at least one of a poly(methylsilsesquioxane) block and a poly(phenylsilsesquioxane) block. [4] The composition according to [1], wherein the concentration of the polydisiloxane block is 0.1 mole percent to 50 mole percent of the polysiloxane resin. [5] The composition according to [1], wherein the polydisiloxane block in the composition has a weight average molecular weight of 100 Da to 5,000 Da. [6] The composition according to [1], wherein the at least one polysiloxane resin is a first polysiloxane resin and further comprises a second polysiloxane resin, the second polysiloxane resin being a poly(silsesquioxane) resin. [7] 1. A method for producing a planarizing composition, comprising: Dissolving at least one polysiloxane resin in one or more solvents to form a resin solution, the at least one polysiloxane resin comprising a polysilsesquioxane block and a polydisiloxane block, the polydisiloxane block having a general formula:

change

change

[10] The planarization film according to [9], wherein the polydisiloxane block comprises at least one of a poly(diphenylsiloxane) block, a poly(phenylmethylsiloxane) block, and a poly(dimethylsiloxane) block.

Claims

1. A composition for planarizing a surface of a semiconductor device, comprising: A catalyst; at least one solvent comprising at least one of ethyl lactate, propylene glycol propyl ether, propylene glycol monomethyl ether acetate, ethanol, isopropyl alcohol, and n-butyl acetate; A first polysiloxane resin comprising a polysilsesquioxane block and a polydisiloxane block, the polydisiloxane block having a general formula: 【Chemistry 1】 This is due to In the formula, R 1 , R 2 are each independently selected from the group consisting of substituted or unsubstituted carbon-containing aryl or alkyl groups; a first polysiloxane resin, the concentration of the polydisiloxane blocks being between 10 mole percent and 35 mole percent of the first polysiloxane resin, the polydisiloxane blocks consisting of poly(diphenylsiloxane) blocks and poly(phenylmethylsiloxane) blocks; a second polysiloxane resin comprising polysilsesquioxane and / or poly(dimethylsiloxane) blocks.

2. The composition of claim 1 , wherein the second polysiloxane resin comprises a polysilsesquioxane block.

3. The composition of claim 1, wherein the second polysiloxane resin comprises a poly(dimethylsiloxane) block and a polysilsesquioxane block.

4. The composition described in any one of claims 1 to 3, wherein the polysilsesquioxane block of the first polysiloxane resin and, when the second polysiloxane resin comprises a polysilsesquioxane block, the polysilsesquioxane block of the second polysiloxane resin comprises at least one of a poly(methylsilsesquioxane) block and a poly(phenylsilsesquioxane) block.

5. The composition of claim 1 , wherein the second polysiloxane resin comprises poly(dimethylsiloxane) blocks.

6. The composition of any one of claims 1 to 5, wherein the weight average molecular weight of the polydisiloxane blocks in the composition is from 100 Da to 5,000 Da.

7. The composition of any one of claims 1 to 6, wherein the catalyst comprises at least one of tetramethylammonium acetate, tetramethylammonium hydroxide, tetrabutylammonium acetate, cetyltrimethylammonium acetate, and tetramethylammonium nitrate.

8. 8. The composition of claim 7, wherein the catalyst is tetramethylammonium nitrate.

9. The composition according to any one of claims 1 to 8, further comprising a surfactant.

10. The composition of any one of claims 1 to 9, further comprising a crosslinking agent.

11. 1. A method for producing a planarizing composition, comprising: Dissolving a first polysiloxane resin and a second polysiloxane resin in one or more solvents to form a resin solution, the first polysiloxane resin comprising a polysilsesquioxane block and a polydisiloxane block, the polydisiloxane block having a general formula: 【Chemistry 2】 This is due to In the formula, R 1 , R 2 are each independently selected from the group consisting of substituted or unsubstituted carbon-containing aryl or alkyl groups; a concentration of the polydisiloxane blocks is from 10 mole percent to 35 mole percent of the first polysiloxane resin, the polydisiloxane blocks consisting of poly(diphenylsiloxane) blocks and poly(phenylmethylsiloxane) blocks; the second polysiloxane resin comprises polysilsesquioxane and / or poly(dimethylsiloxane) blocks; forming a solution comprising one or more solvents comprising at least one of ethyl lactate, propylene glycol propyl ether, propylene glycol monomethyl ether acetate, ethanol, isopropyl alcohol, and n-butyl acetate; adding a catalyst to the resin solution.

12. A planarization film for a semiconductor device, comprising: Catalyst residue; A cured polysiloxane comprising a first polysiloxane resin and a second polysiloxane resin, the first polysiloxane resin comprising a polysilsesquioxane block and a polydisiloxane block, the polydisiloxane block having a general formula: 【Chemistry 3】 This is due to In the formula, R 1 , R 2 are each independently selected from the group consisting of substituted or unsubstituted carbon-containing aryl or alkyl groups; a cured polysiloxane, the concentration of the polydisiloxane blocks being 10 mole percent to 35 mole percent of the first polysiloxane resin, the polydisiloxane blocks being comprised of poly(diphenylsiloxane) blocks and poly(phenylmethylsiloxane) blocks, and the second polysiloxane resin being comprised of polysilsesquioxane and / or poly(dimethylsiloxane) blocks; A planarizing film comprising:

13. 13. The planarizing film of claim 11 or 12, having a thickness of 5 μm or more.

Citation Information

Patent Citations

  • Production of heat-resistant resin composition and insulation film

    JP1992185641A

  • Preparation of film-forming composition

    JP2000302869A

  • Coating composition and display device using the same

    JP2006083319A

  • Polysiloxane formulations and coatings for optoelectronic applications

    WO2016167892A1